A Review On Nutritional Composition And Heavy Metal Content In Malaysia Aquaculture Products - Ting, Zhao Jing (Universiti Sains Malaysia, 2021)
Malaysia aquaculture industry had shown rapid development correlating to the rising demand of fisheries products. Aquaculture products form a nutritious part in human diet with its balanced composition of proteins, lipids, fatty acids, vitamins and minerals. This research aimed to evaluate the nutritional composition and heavy metal content in Malaysia aquaculture products. Nutritional composition of 18 aquaculture products, including 10 finfish, 3 crustaceans, 2 molluscs, and 3 seaweeds from freshwater and brackishwater were determined. All selected species had high protein content (12.02–23.0%) except seaweeds. However, seaweeds had the most carbohydrates content (41.52–66.66%) among all species. Freshwater species consisted of more omega-6 polyunsaturated fatty acids (PUFAs) than brackishwater species but omega-3 PUFAs in brackishwater species were greater than most freshwater species due to high eicosapentaenoic and docosahexaenoic acid contents. Omega-6/omega-3 ratio of all species was modest (0.23–6.94) except for red tilapia (10.18). Vitamin content in all species were minimal except for snapper having high vitamin D3 content (10.2 μg/100 g). Shellfish contained significant amounts of calcium (52–142 mg/100 g) while freshwater finfish contained high amount of phosphorus (200 mg/100 g). Meanwhile, brackishwater shellfish and seaweeds were rich source of iron (5.09 mg/100 g) whereas brackishwater finfish were a rich source of iodine. In terms of heavy metal content, arsenic was found higher in brackishwater fish (0.74 – 4.52 μg/g) than freshwater fish (0.02 – 1.07 μg/g) but the highest was found in seaweeds (4.47 μg/g). Regardless of the location of aquaculture sites, all lead content of green mussel (2.51–7.98 μg/g) exceeded the permissible limit (0.5–2 μg/g). Shellfish showed considerably higher heavy metal content, particularly copper and lead, than all other selected species. No species were identified to have exceeded the permissible limit for mercury.